2019
DOI: 10.1167/iovs.19-28082
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Endogenous SDHA Drives Pathological Metabolism in Highly Metastatic Uveal Melanoma

Abstract: PurposeMetastatic uveal melanoma (UM) has a very poor prognosis and no effective therapy. Despite remarkable advances in treatment of cutaneous melanoma, UM remains recalcitrant to chemotherapy, small-molecule kinase inhibitors, and immune-based therapy.MethodsWe assessed two sets of oxidative phosphorylation (OxPhos) genes within 9858 tumors across 31 cancer types. An OxPhos inhibitor was used to characterize differential metabolic programming of highly metastatic monosomy 3 (M3) UM. Seahorse analysis and glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Altered metabolism is a hallmark of cancer [ 46 ] and oxidative phosphorylation has emerged as a therapeutic strategy [ 47 ]. Comparing 31 tumour types, UM ranked amongst the tumours with the highest oxidative phosphorylation signature [ 48 ]. To determine if the effects of CysLT 1 antagonists were due to altered metabolism in UM cells, the Seahorse Assay was performed assessing two key metabolic pathways: oxidative phosphorylation and glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Altered metabolism is a hallmark of cancer [ 46 ] and oxidative phosphorylation has emerged as a therapeutic strategy [ 47 ]. Comparing 31 tumour types, UM ranked amongst the tumours with the highest oxidative phosphorylation signature [ 48 ]. To determine if the effects of CysLT 1 antagonists were due to altered metabolism in UM cells, the Seahorse Assay was performed assessing two key metabolic pathways: oxidative phosphorylation and glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…These metabolic pathways have already been linked to immune-resistance to checkpoint inhibitors in different studies [ 34 , 36 , 37 , 38 ]. Interestingly, a recent study has shown that UM is among the tumors with the highest oxidative phosphorylation gene expression and correlates with prognosis in primary UM [ 39 ]. Our group has recently made the same observation in MUM patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene set enrichment analyzes (GSEA) on DEGs and PC1/PC2 ( figure 4E, online supplemental figure 3) demonstrated increased expression of hallmark gene sets involved in metabolic pathways, such as oxidative phosphorylation (OXPHOS), xenobiotic metabolism and fatty acid metabolism in UM. It has previously been described that UM is ranked among the tumors with the highest OXPHOS signature, 62 and this property has been associated with invasiveness and drug resistance. 63 Pathways upregulated in CM involved proliferation (mitotic spindle, E2F targets, MYC targets and G2M checkpoint) and immune pathway (tumornecrosefactor-alfa (TNFA) signaling via NFKB) ( figure 4E).…”
Section: And Um Liver Metastases Show Differences At the Transcripmentioning
confidence: 98%